SOSIALISASI PEMANFAATAN MINYAK JELANTAH MELALUI PEMBUATAN LILIN AROMATERAPI DI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Yunita, Imelda; Iqbal, Muhammad; Novita, Dea; Wakaifah, Muskylatul; Mitrajati, Mitrajati; Aini, Zamratul; Rahmayani, Shintya; Novriani, Anggi; Pradana, Muhammad Arya (Universitas Teknokrat Indonesia, 2024)
The purpose of this socialization activity is to raise awareness among the community of Rambah Baru Village about the dangers of using used waste cooking oil and to provide an alternative way to utilize this waste through the production of aromatherapy candles. The methods used in this socialization include delivering materials and demonstrating the production of aromatherapy candles, and giving souvenirs to the participants. The results of this activity show that the community not only gains knowledge about the negative impacts of cooking oil waste but also practical skills that can enhance creative economy. The production of aromatherapy candles from used cooking oil is expected to reduce environmental pollution and provide economic value for the local community. Thus, this activity represents a positive step in community service and entrepreneurship development in the village.Keyword: Socialization, aromatherapy, candles